2008
DOI: 10.1002/jhet.5570450312
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and pharmacological investigation of novel 4‐(4‐Ethyl phenyl)‐1‐substituted‐4H‐[1,2,4]triazolo[4,3‐a]‐quinazolin‐5‐ones as new class of H1‐antihistaminic agents

Abstract: The first generation antihistamines penetrate the blood brain barrier and also possess anticholinergic properties; this has led to the development of a second generation of H 1 -antagonists such as terfenadine, cetirizine and astemizole (1). A common feature of the first generation compounds includes two aryl or heteroaryl rings linked to an ali-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 11 publications
0
4
0
2
Order By: Relevance
“…Interaction of the quinazolinone 3 with aldehydes in glacial acetic acid affording (E) 2-(1-aryl)but-1-en-2yl)quinazolin-4(3H)-one (8a-d). On the other hand, the ester 4 was treated with hydrazine hydrate afforded the corresponding hydrazide derivatives (9). Compound (9) was used for the synthesis of diverse heterocyclic compound, thus when compound (9) was allowed to react with boiling acetic anhydride yielding 3 -( ( 5-methyl-1, 3, 4 -oxadiazol-2 -yl ) methyl)-2-propylquinazolin-4(3H)one (10).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interaction of the quinazolinone 3 with aldehydes in glacial acetic acid affording (E) 2-(1-aryl)but-1-en-2yl)quinazolin-4(3H)-one (8a-d). On the other hand, the ester 4 was treated with hydrazine hydrate afforded the corresponding hydrazide derivatives (9). Compound (9) was used for the synthesis of diverse heterocyclic compound, thus when compound (9) was allowed to react with boiling acetic anhydride yielding 3 -( ( 5-methyl-1, 3, 4 -oxadiazol-2 -yl ) methyl)-2-propylquinazolin-4(3H)one (10).…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of quinazolinone heterocycles has become the cornerstone for synthetic chemists and gained extensive importance in medicinal chemistry because of their diverse pharmacological activities including antimycobacterial (1,2) , antimalarial (3) , antihypertensive (4) , antihistaminic (5)(6)(7)(8)(9) , local anesthetic (10) , antiparkinson (11) , cardiotonic (12) , anticancer (13)(14)(15)(16) , antiviral (17) and thymidylate synthase inhibitory activities (18) . Several simple and condensed quinazolines are also known to exhibit potent CNS activities as analgesic (19,20) , anti-inflammatory (21,22) and anticonvulsant activities (23,24) .…”
mentioning
confidence: 99%
“…Compound ( [66][67][68]. It was found that by varying substitution over the first position of the triazolo quinazoline (52) ring there was variation in the biological activity.…”
Section: Compound 50mentioning
confidence: 99%
“…Похідні хіназолін-4-ону з анельованими гетероциклами проявляють антигістамінну [6][7][8][9], антигіпертензивну [10][11][12], протиракову цітотоксичну [13] та антибактеріальну і антигрибкову [5] активність. Тому метою даної роботи стала розробка зручного методу синтезу 3-заміщених 2-гідразинохіназолін-4-онів для подальшого використання їх в якості синтонів для отримання похідних хіназолін-4-ону з анельованими гетероциклами.…”
Section: Issn 2308-8303unclassified
“…Відповідні 2-тіоксохіназолін-4-они 3 легко отримують при взаємодії естерів 2-ізо-тіоціанатобензойних кислот 1 з первинними амінами [5]. Найлегше заміщення відбувається при використанні 2-алкілтіохіноксалін-4-онів 4 [7][8][9]. Але в цьому випадку видаляється токсичний та сморідний алкілмеркаптан, що може завдати проблем при великих масштабах синтезу, та ця схема має додаткову стадію алкілювання 2-тіоксохіназолін-4-ону.…”
Section: результати та їх обговоренняunclassified